Tijuana's Dynamic Unemployment and Output Growth - Díaz-Bautista, Alejandro (Frontera Norte, 2017)
During the 1990s, Mexico successfully implemented a program of economic reforms and free trade aimed at a complete restructuring of its economy. Surprisingly, the reform process seems to have had little impact on unemployment. An analysis of trends indicates that, even in the worst years of economic crisis, average unemployment rates in Mexico did not exceed 7.4% (reached in the third quarter of 1995). Tijuana's unemployment rate averaged 0.725% in 2001, when the economy was experiencing the start of a recession and major structural reforms were expected. These figures seem very low when compared to those for other countries. This article's goal is to evaluate transitory demand shocks and permanent supply shocks in Tijuana's unemployment time series, as given by that identification restriction and the structural break unit root methodology. Okun's Law is also tested for the Tijuana unemployment series. RESUMEN En la década pasada, México estableció un programa de reformas económicas y de libre comercio encaminadas a la completa reestructuración de su economía. Sorprendentemente, el proceso de reforma tiene poco impacto en el desempleo. Un análisis de las tendencias indica que, aun en los peores trimestres de la crisis económica, la tasa de desempleo promedio no fue mayor de 7.4%. La tasa de desempleo trimestral de la ciudad de Tijuana en 2001 alcanzó en promedio 0.725%, en un período donde inició una recesión en la economía. Estas cifras son bajas al ser comparadas con las de otros países. El objetivo del estudio es evaluar los choques transitorios de la demanda y los permanentes de la oferta en el desempleo en Tijuana en diferentes períodos. Para ello utiliza la restricción de identificación y la metodología de raíz unitaria con corte estructural. La ley de Okun también es verificada para conocer la evolución del desempleo en Tijuana.